Synthesis of hydroxyapatite-zeolite from blast furnace slag and its application for the removal of copper, lead and copper-lead mixture by adsorption - Toufik Chouchane; Mohamed Tayeb Abedghars; Sabiha Chouchane; Atmane Boukari (Advances in Environmental Technology)
This article sheds light on the applications of hydroxyapatite-zeolite (HZ) from a steelmaking by-product, namely treated blast-furnace slag (TBFS), in the adsorption of copper, lead and copper-lead mixture in batch mode. Chemical and spectral analysis showed that sodium oxide, silicon dioxide, aluminum oxide, calcium oxide, and phosphorus hemi-pentoxide are the main constituent elements of HZ. After conversion of TBFS to HZ, the specific surface area experienced a significant expansion from 275.8 to 409.63 m2/g, while the point of zero charge (PZC) regressed from 3.8 to 3.4 on the pH scale. The sodium oxide/alumina, lime/phosphorus pentoxide, and silica/alumina ratios, estimated at 1.71, 1.61, and 1.31, respectively, indicate that the slag was transformed into hydroxyapatite-zeolite. The tests revealed that the impact of contact time (50 min), HZ mass (1g), solution agitation (200 rpm), solution pH (5), medium temperature (20 °C), HZ particle size (250µm) and initial concentration of the pollutant solution (240 mg/L) significantly improved the efficiency of these processes, where the adsorption power of copper, lead and mixture reached 124.87 mg/g, 115.14 mg/g and 108.74 mg/g, respectively. The adsorption isotherms demonstrated that the processes in question occurred on a homogeneous surface covered with a single layer, as evidenced by the correlation coefficients and the capacities of adsorption. The kinetic models demonstrated that the sorption processes undertaken obeyed pseudo-second-order kinetics (R² ≥ 0.99). Examination of the adsorption mechanism highlighted that these processes are regulated by various external and internal diffusions. Thermodynamic evaluations confirmed that ongoing procedures are characterized by heat release (exothermic). In addition, they demonstrate their spontaneous character, which is less disordered and results from physical interactions (physical adsorption). It has been demonstrated by the desorption process that HZ can be reused for 6 successive cycles.